2010
DOI: 10.3354/dao02218
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of black bullhead Ameiurus melas to a panel of ranavirus isolates

Abstract: Ranaviruses are considered a serious threat to lower vertebrates, including fish, amphibians and reptiles. However, epidemiological data on these agents are lacking, and further investigations are needed to understand the role of carriers and to update the list of susceptible hosts. We carried out various experimental infections under controlled conditions to contribute to the current knowledge on the susceptibility of black bullhead Ameiurus melas to European catfish virus (ECV) and other ranaviruses. A panel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 31 publications
3
32
1
Order By: Relevance
“…The virus is readily transmitted to catfi sh via a range of challenge methods including bath exposure, cohabitation, and intramuscular injection (Ahne et al 1990 ;Pozet et al 1992 ), and results in only a small proportion of exposed catfi sh surviving (Pozet et al 1992 ). Interestingly, Gobbo et al ( 2010 ) found different patterns of susceptibility based on closely related ranavirus strains, as black bullheads were susceptible to ECV, but not to the ESV isolate used in this study. More recent experiments have demonstrated variable pathogenicity of different isolates of ECV, and a strong impact of water temperature on disease outcome, with mortality varying between 8 and 10 % among challenged sheatfi sh (Leimbach et al 2014 ).…”
Section: European Catfi Sh Virusmentioning
confidence: 73%
See 1 more Smart Citation
“…The virus is readily transmitted to catfi sh via a range of challenge methods including bath exposure, cohabitation, and intramuscular injection (Ahne et al 1990 ;Pozet et al 1992 ), and results in only a small proportion of exposed catfi sh surviving (Pozet et al 1992 ). Interestingly, Gobbo et al ( 2010 ) found different patterns of susceptibility based on closely related ranavirus strains, as black bullheads were susceptible to ECV, but not to the ESV isolate used in this study. More recent experiments have demonstrated variable pathogenicity of different isolates of ECV, and a strong impact of water temperature on disease outcome, with mortality varying between 8 and 10 % among challenged sheatfi sh (Leimbach et al 2014 ).…”
Section: European Catfi Sh Virusmentioning
confidence: 73%
“…Although there are recognized defi ciencies in laboratory challenge models to determine the susceptibility of host fi sh to virus isolates under natural conditions, a potential increase in the host range of EHNV infections has been predicted. In three separate challenge studies, black bullhead ( Ameiurus melas ), pike ( Esox Lucius ), and pike-perch ( Sander lucioperca ) experienced signifi cant mortality following bath exposure to EHNV , 2011aGobbo et al 2010 ). On the other hand, goldfi sh ( Carassius auratus ), common carp ( Cyprinus carpio ), and European sheatfi sh ( Silurus glanis ) did not experience signifi cant mortality following bath exposure to EHNV (Bang-Jensen et al 2011b ;Leimbach et al 2014 ).…”
Section: Epizootic Haematopoietic Necrosis Virusmentioning
confidence: 99%
“…Until the recent studies by Brenes et al ( 2014a , b ), comparative studies involving reptiles were generally lacking, and those involving fi sh are largely restricted to EHNV (Becker et al 2013 ;Langdon 1989 ; but see Brenes et al 2014b ). Note, however, that several recent studies have exposed different fi sh species to multiple ranaviruses from fi sh and amphibians, so collectively information is accumulating on the relative susceptibility of fi sh (Bang Jensen et al 2009, 2011aGobbo et al 2010 ;Brenes et al 2014b ).…”
Section: Susceptibility To Ranaviruses Among Speciesmentioning
confidence: 99%
“…For example, morbid fi sh and turtles have been reported in association with amphibian die-offs due to ranaviral disease Farnsworth and Seigel 2013 ). Moreover, several laboratory studies have demonstrated that BIV and FV3-like viruses isolated from one vertebrate class could be used to experimentally infect animals in another (Moody and Owens 1994 ;Ariel and Owens 1997 ;Bang Jensen et al 2009, 2011bGobbo et al 2010 ;Bayley et al 2013 ;Brenes et al 2014b ). Recently, Brenes et al ( 2014a ) paired ranavirus-exposed and -unexposed hosts from different vertebrate classes on opposite sides of a fi ne mesh screen, preventing direct contact but allowing water and virions to pass through.…”
Section: Ranavirus Transmission Between Speciesmentioning
confidence: 99%
See 1 more Smart Citation